Relatively Unworthy Victims? Middle-Aged Women as Rape Survivors - Kwon, Minju (Violence against women, 2024)
This study examines how the age of female survivors impacts public perceptions of rape in China. In our online survey experiment, participants consider rape as less serious when the survivor is a middle-aged woman compared to other groups of women (younger, older, or age unknown). Participants also request shorter sentencing when the survivor is a middle-aged woman than a younger woman. In China, moral codes surrounding chastity and respect for elders lead to greater emotional responses toward rape against younger and older survivors than middle-aged survivors. Our study expands studies of rape perception by theorizing public attitudes toward middle-aged survivors.